Narrative Formation as a tool to influence Public Sentiment – The Case of Volkswagen’s Diesel Emissions Scandal - Muhammad Kamran Bais; Kashmala Zaman (Social Science Review Archives, 2025)
Volkswagen group (also known as Volkswagen AG) is home to some of biggest and most successful automotive brands in the world. In September 2015, the organization came under scrutiny when it was uncovered that Volkswagen had been manipulating data to illegally pass emission tests in the US for its diesel cars. This was a major crisis for the organization which ended up in several legal charges and costing the company billions of dollars. Several high-ranking executives, including the then CEO of Volkswagen were also indicted both in the US and in Germany. This research analyses news articles from reputable news sources that reported on the scandal in order to understand how the sentiment towards the organization changed over time. This research sheds light on how Volkswagen AG was able to distance itself and its brands from this infamous emissions scandal that received global criticism. The research uses content analysis to analyze secondary data from reputable news sources to achieve the research aim.